Design and optimization of planetary gear train pendulum type sugarcane seeding mechanism based on spatial offset trajectory - Jiaodi Liu; Chaoyuan Luo; Qingli Chen; Jianhao Chen; Jianlong Chen; Yihao Xing (AIP Advances)
The existing sugarcane seeding mechanisms cannot clamp the sugarcane seeds to complete complex spatial motion trajectories and postures. This leads to poor stability of the sugarcane seed fall, and the seeding fails to meet the agronomic requirements of offset sugarcane seeding. Therefore, a secondary elliptical planetary gear train pendulum-type sugarcane seeding mechanism is proposed. A spatial inverse kinematics model is established with the pre-planned spatial motion trajectories as constraints, and the lengths of each rod are inversely solved. By determining the motion position and posture of the pendulum that clamps the sugarcane seeds, and combining with the spatial position geometric transformation model, the relative position relationship between the input shaft and the output shaft is solved. Using the limitation of the secondary gears on the motion freedom of the rods, the transmission ratios of this planetary gear train are assigned to design the structural dimensions of each gear. Based on the speed requirements of the sugarcane seeds at the critical motion points, a forward kinematics model of this seeding mechanism is established. A multi-objective genetic algorithm combined with the entropy-weight TOPSIS method is used to optimize and screen the installation dimensions of the components of the mechanism so as to keep the motion of the sugarcane seeds stable at the critical positions. In the writing of this paper, the first author provided the working conditions, while the other authors were responsible for writing, experimental verification, translation, and other tasks. The simulation verification results show that the motion trajectory postures of the virtual prototype are basically consistent with the theoretical model, meeting the agronomic requirements of offset sugarcane seeding and verifying the feasibility of the mechanism design.